Borrelia miyamotoi: 43 Cases Diagnosed in France by Real-Time PCR in Patients With Persistent Polymorphic Signs and Symptoms - Franck, Michel; Ghozzi, Raouf; Pajaud, Julie; Lawson-Hogban, Nadou E.; Mas, Marie; Lacout, Alexis; Perronne, Christian (Frontiers in Medicine, 2020)
Background: Borrelia species are divided into three groups depending on the induced disease and the tick vector. Borrelia miyamotoi is a relapsing fever Borrelia but can induce symptoms related to Lyme disease. Discovered in 1995, it is found in ticks around the world. In France, this species of Borrelia has been isolated in ticks and rodents, but was not yet observed in humans. Objective: The aim of the study was to look for B. miyamotoi in symptomatic patients. Methods: Real-time PCR was performed on 824 blood samples from patients presenting symptoms of persistent polymorphic syndrome possibly due to tick bite, a syndrome recognized by the French Authority for Health, which is close to the post-treatment Lyme disease syndrome. PCR was also performed on 24 healthy control persons. The primers were specifically designed for this particular species of Borrelia. The sequence of interest of 94 bp is located on the glpQ gene. Sequencing of amplification products, randomly chosen, confirmed the amplification specificity. To better investigate cases, a clinical questionnaire was sent to the patients PCR-positive for B. miyamotoi and to their physician. Results: This search revealed a positive PCR for B. miyamotoi in the blood from 43 patients out of 824 (5.22%). PCR was negative in all control persons. A clinical chart was obtained from 31 of the 43 patients. A history of erythema migrans was reported in 5 of these 31 patients (16%). All patients complained about fatigue, joint pain and neuro-cognitive disorders. Some patients complained about respiratory problems (chest tightness and/or lack of air in 41.9%). Episodes of relapsing fever were reported by 11 of the 31 patients (35.5%). Chilliness, hot flushes and/or sweats were reported by around half of the patients. B. miyamotoi may not cross-react with B. burgdorferi serology. Conclusion: This study is the first to detect B. miyamotoi in human blood in France. This series of human B. miyamotoi infection is the largest in patients with long term persistent syndrome. Our data suggest that this infection may be persistent, even on the long term.